Effect of Addition of Dexamethasone to Local Anaesthetics in Supraclavicular Brachial Plexus Block - Islam, SM; Hossain, MHMD; Maruf, AA (Journal of Armed Forces Medical College, Bangladesh, 2011)
Introduction: Many-a-time local anaesthesia appears as a very effective alternative of general one. Different additives have been used to prolong regional blockade. Objective: This prospective study designed to evaluate the effect of dexamethasone added to local anaesthetics on the onset and duration of supraclavicular brachial plexus block. Methods: Sixty adult patients undergoing various orthopaedic surgeries on forearm and around the elbow under supraclavicular brachial plexus block were selected and divided into 2 groups of 30 each. In group-A patients received 35 ml of mixture of lignocaine 2%, bupivacaine 0.5% while in group-B patients received the same amount of local anaesthetics with dexamethasone (8 mg). The onset of sensory and motor block and duration of analgesia in two groups were compared and development of complications were observed. Result: The two groups were comparable in demographic data. The mean onset time of sensory block was 11.64±2.19 minutes in group A and 9.89±1.97 minutes in group B and difference was statistically significant (p<0.05). Onset of motor block was 13.32±0.98 minutes in group A and 11.09±1.28 minutes in group B and difference was statistically significant (p<0.05). There was markedly prolonged duration of analgesia in group-B, 11.87± 0.53 hours compared to group-A, 3.43±0.49 hours. The result was statistically highly significant (p<0.001). Both the groups had high success rate (>90%). The incidence of complication was low in both the groups. Conclusion: Addition of dexamethasone as an adjuvant to local anaesthetics in brachial plexus block results in significantly early onset and markedly prolonged duration of analgesia without any unwanted effects. Key words: Supraclavicular block; analgesia; local anaesthetics; dexamethasone DOI: http://dx.doi.org/10.3329/jafmc.v7i1.8619 JAFMC Bangladesh. Vol 7, No 1 (June) 2011; 11-14